A novel, green and affordable semi-quantitative limit test for 2-aminobutanol impurity in ethambutol hydrochloride bulk and tablets - Thana Thanayutsiri; Prasopchai Patrojanasophon; Praneet Opanasopit; Tanasait Ngawhirunpat; Theerasak Rojanarata (Pensoft Publishers, 2024)
The pharmacopoeial limit test for the impurity 2-aminobutanol (AB) in ethambutol hydrochloride (ETB) relies on florescence measurement using a fluorometer. However, this instrument is often unavailable in many laboratories due to its cost. A novel colorimetric method was therefore developed using genipin, an amine-reactive reagent, to react with AB, producing a blue color. The color intensity was subsequently measured using a more affordable UV-vis spectrophotometer. To overcome matrix effects, the standard addition technique was incorporated. The test effectively detected AB at concentrations as low as 0.125% in ETB, below the compendial limit of 1.0%. The analysis of ETB bulk and tablets showed consistent semi-quantitative results with the USP method. Furthermore, it aligned with green chemistry by eliminating the use of organic solvents and employing safe, naturally derived reagent. In summary, the proposed method provides a reliable, green, and cost-effective alternative for analyzing AB in ETB, ensuring compliance with pharmacopeial standards.